A Plastic Vegetative Growth Threshold Governs Reproductive Capacity in Aspergillus nidulans. Issue 3 (1st November 2016) - Noble, Luke M; Holland, Linda M; McLauchlan, Alisha J; Andrianopoulos, Alex
Abstract: Ontogenetic phases separating growth from reproduction are a common feature of cellular life. Long recognized for flowering plants and animals, early literature suggests this life-history component may also be prevalent among multicellular fungi. We establish the basis of developmental competence—the capacity to respond to induction of asexual development—in the filamentous saprotroph Aspergillus nidulans, describing environmental influences, including genotype-by-environment interactions among precocious mutants, gene expression associated with wild type and precocious competence acquisition, and the genetics of competence timing. Environmental effects are consistent with a threshold driven by metabolic rate and organism density, with pH playing a particularly strong role in determining competence timing. Gene expression diverges significantly over the competence window, despite a lack of overt morphological change, with differentiation in key metabolic, signaling, and cell trafficking processes. We identify five genes for which mutant alleles advance competence timing, including the conserved GTPase RasB (AN5832 ) and ambient pH sensor PalH (AN6886 ). In all cases examined, inheritance of competence timing is complex and non-Mendelian, with F1 progeny showing highly variable transgressive timing and dominant parental effects with a weak contribution from progeny genotype. Competence provides a new model for nutrient-limited life-cycle phases, and their elaboration from unicellular origins. Further work is required to establish the hormonal and bioenergetic basis of the trait across fungi, and underlying mechanisms of variable inheritance.